IDENTIFICATION OF FACTORS CONTRIBUTING TO STUDENTS’ DIFFICULTIES IN SOLVING CONTEXTUAL PROBLEMS ON CIRCLE TOPICS USING THE FISHBONE DIAGRAM METHOD - Kowi, Mohamad Saiful; Dewi, Irmawati Liliana Kusuma (Jurnal Pendidikan Matematika dan IPA, 2026)
Mathematical problem solving ability is an important skill for students to face real-world challenges. One material that is closely related to everyday life is circles. However, in practice, many learners have difficulty linking the concept of circles with contextual situations, resulting in their low problem-solving ability. This gap shows the importance of in-depth analysis of the factors that cause these difficulties. This study aims to systematically identify the factors that cause students"™ difficulties in solving contextual problems of circle material using the Fishbone Diagram method. The type of research is descriptive with a qualitative approach involving 23 students of class XI.11 SMA Negeri 7 Cirebon City who were selected through purposive sampling. Data were collected through observation, interviews, and literature studies. The data analysis technique used the Miles and Huberman model and the Fishbone Diagram method. The results grouped the difficulty factors into five main categories, namely: Man (understanding of problems and formulas, lack of confidence, difficulty connecting concepts, lack of initiative to ask, and limited teacher guidance), Method (dominant lecture method, minimal contextual exercises, lack of group discussions), Material (learning resources do not contain contextual problems, lack of interactive media assistance, examples of problems are less varied), Environment (less conducive classroom environment), and Measurement (exam questions are more difficult than exercises and lack of exam time). These results show that learners"™ difficulties are influenced by internal and external factors simultaneously. This study recommends the need to develop learning strategies that are more contextual, interactive, and create a more supportive learning environment to strengthen students"™ critical thinking and applicative skills.